2007
DOI: 10.2217/14796708.2.4.451
|View full text |Cite
|
Sign up to set email alerts
|

Post-polio syndrome: clinical manifestations and cerebrospinal fluid markers

Abstract: Post-polio syndrome (PPS) refers to a constellation of new neurological, musculoskeletal and general symptoms occurring in survivors of poliomyelitis decades after acute paralytic and nonparalytic disease. The common manifestations of PPS include generalized, central and peripheral fatigue, muscle weakness and musculoskeletal pain. The pathogenesis of PPS remains obscure. Three prevailing hypotheses have been advanced: stress-induced degeneration of surviving neurons, persistent poliovirus replication or virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…We previously showed that 14-3-3 was positive in the CSF of neuroleptic-treated patients [13], as well as other neurologic and inflammatory diseases, such as Guillain Barrè syndrome [14], post-polio syndrome [15], acute myelitis [16], and multiple sclerosis [17]. Most of these CSF samples had normal tau levels, likely because the degree of neuronal or axonal damage was not severe enough to determine an increase in released tau protein in the CSF [13].…”
Section: Discussionmentioning
confidence: 98%
“…We previously showed that 14-3-3 was positive in the CSF of neuroleptic-treated patients [13], as well as other neurologic and inflammatory diseases, such as Guillain Barrè syndrome [14], post-polio syndrome [15], acute myelitis [16], and multiple sclerosis [17]. Most of these CSF samples had normal tau levels, likely because the degree of neuronal or axonal damage was not severe enough to determine an increase in released tau protein in the CSF [13].…”
Section: Discussionmentioning
confidence: 98%
“…There are no diagnostic tests or specific biomarkers for PPS. 22,66,67 The early diagnostic criteria of Halstead represent the basis of the criteria presented by Trojan and Cashman 68 have been integrated into current diagnostic guidelines: 22 (1) Prior paralytic poliomyelitis with evidence of motor neuron loss, as confirmed by history of the acute paralytic illness, signs of residual weakness, and atrophy of muscles on neurological examination, and signs of denervation on electromyography. (2) A period of partial or complete functional recovery after acute paralytic poliomyelitis, followed by an interval (usually 15 years of more) of stable neurological function.…”
Section: Diagnostic Criteria For Ppsmentioning
confidence: 99%
“…About two to three decades after the acute episode, there is a tendency to overload this system, that can be accelerated depending on individual factors especially the activities and exercises carried out that promote overuse of the affected muscles. In this case of overuse and super training , an intense metabolic demand in the residual motor units occurs, which then triggers a process of secondary neuronal death (Orsini et al, 2015), and active inflammatory process is present in the spinal cord with increased level of cytokines in the cerebrospinal fluid but without any convincing evidence of viral reactivation (Fiorini et al, 2007).…”
Section: Introductionmentioning
confidence: 99%